DAMPAK PANDEMI COVID-19 TERHADAP IMPLEMENTASI MAKING INDONESIA 4.0 - Shiddiq Ardhi Irawan (Direktorat Jenderal Anggaran Kementerian, Keuangan Republik Indonesia, 2021)
The industrial revolution is a process of change in which human work in various fields is replaced by machines. Currently the world has entered the era of the industrial revolution 4.0 so that the process of producing goods or services is much more efficient than before. Therefore, since 2017 the Ministry of Industry has made a roadmap for the Implementation of Making Indonesia 4.0 to accelerate the development of the manufacturing industry in Indonesia. In the process of achieving this goal, Indonesia is one of the countries most affected by the COVID-19 pandemic which began in early 2020. The activity plans that have been prepared in the roadmap must be adjusted because most of their budget has been reallocated or refocused for handling the impact of the COVID-19 pandemic. -19, this study aims to determine the implementation of Making Indonesia 4.0 on the impact of the covid-19 pandemic in terms of policies and budget allocations. The method used is a literature study and descriptive analysis using quantitative and qualitative data types. Based on the results of the descriptive analysis, information was obtained that the 2020 budget allocation for the Implementation of Making Indonesia 4.0 included the refocusing of 63.4% of the initial ceiling. With this refocusing, it is necessary to reconstruct the national priority programs contained in the roadmap for the Implementation of Making Indonesia 4.0 and redesign. financing so that not all national programs use the state budget.